Perlindungan Hukum terhadap Saksi Pelapor dalam Proses Persidangan di Bawaslu - Suryani, Lilis; Rasyid, Muh Fadli Faisal; Nasir, Muh; Suprapto, Suprapto; Daud, Fadly; Sahrir, Salman; Latif, Asriyadi; Purwanda, Nur Widia (Amsir Law Journal, 2024)
The lack of specific regulations regarding the protection of whistleblowers in Law Number 10 of 2016 and Law Number 7 of 2017, apparently intersects with the issue of mechanisms and procedures for the protection of whistleblowers. The guarantee of protection for whistleblowers in Law No. 31 of 2014 is only on criminal protection. Meanwhile, administrative and ethical violations have not been well accommodated. The focus of related research is to describe the role and responsibility of Election Supervisory Board (Bawaslu) in providing legal protection to the reporting witness during the trial process at Bawaslu. In addition, it is also to find a form of legal protection for the reporting witness during the process at the Bawaslu hearing. Bawaslu plays a role in law enforcement related to general election violations which are administrative, criminal, and code of ethics violations of election organizers. Responsible for handling reports and findings of general election violations by processing and following up in accordance with applicable procedures. Provide recommendations to the authorities to follow up on a violation. Resolving disputes over the electoral process involving election participants, election organizers, or other interested parties. Avoiding the reporting witness from feeling insecure which can also potentially affect public confidence in the integrity of the trial process in Bawaslu. In addition, there is also a need for a correlation between Witness and Victim Protection Agency and Bawaslu to achieve balanced handling and not psychologically harm the reporting witness. ___ Referensi Buku dengan penulis: Theofany, S. (2019). Indeks Kinerja Hak Asasi Manusia Pemerintahan Joko Widodo–Jusuf Kalla, Jakarta: Pustaka Masyarakat Setara. Artikel jurnal: Adhyaksa, G., Fathanudien, A., & Al-azizi, W. A. (2024). Perlindungan Hukum terhadap Saksi Tindak Pidana Korupsi oleh Lembaga Perlindungan Saksi dan Korban (LPSK). Dinamika Hukum Terkini, 6(2), 31-50. https://journalpedia.com/1/index.php/dht/article/view/1048 Awaluddin, M., Siallagan, D. Y., Prestoroika, E., & Qadri, U. (2023). Peran Badan Pengawas Pemilu dalam Penangganan Pelanggaran Pemilu (Studi Kasus Netralitas ASN di Kota Pontianak. Jurnal Perspektif Administrasi dan Bisnis, 4(1), 55-62. https://doi.org/10.38062/jpab.v4i1.454 Darmayanti, Y. P., Sedia, I. W., & Moedy, E. R. S. (2024). Implementasi Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum dalam Memperkuat Lembaga Pengawas Pemilu (Bawaslu) di Kabupaten Badung. Jurnal Ilmiah Cakrawarti, 7(1), 36-41. https://doi.org/10.47532/jic.v7i1.964 Djamaludin, D., & Arrasyid, Y. (2024). Pemenuhan Keadilan Dalam Sistem Hukum Pidana Indonesia Melalui Tugas LPSK. Jurnal Ilmu Hukum Kyadiren, 5(2), 30-44. https://doi.org/10.46924/jihk.v5i2.188 Fachrodin, F. (2019). Efektivitas Kebijakan Hukum Pidana tentang Perlindungan Saksi dalam Proses Peradilan. INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 5(1), 1-12. http://jurnal.iaih.ac.id/index.php/inovatif/article/view/87 Farhati, M. Z., Apriliyani, A., Hernawan, D., & Ramdani, F. T. (2024). Implementasi Penanganan Tindak Lanjut Temuan dan Laporan Dugaan Pelanggaran Pemilu oleh Badan Pengawas Pemilu. Karimah Tauhid, 3(7), 7903-7917. https://doi.org/10.30997/karimahtauhid.v3i7.14271 Firmanto, A. A. (2022). Penanganan Pelanggaran Administrasi Terstruktur Sistematis dan Masif (TSM) dan Masa Depan Demokrasi Lokal di Indonesia. Jurnal Empati Kadarkum, 1(1). 7-16. https://www.ejurnalmalahayati.ac.id/index.php/empatikadarkum/article/view/7427 Hadi, Y. (2024). Pemberian Biaya Penganti terhadap Saksi Perkara Pidana pada Tahap Penyelidikan dan Penyidikan di Polres Aceh Tengah. Cendekia: Jurnal Hukum, Sosial dan Humaniora, 2(3), 673-687. https://doi.org/10.5281/zenodo.12743206 Haryani, R. (2023). Optimalisasi Kewenangan Bawaslu sebagai Lembaga Pengawas Pemilu dan Lembaga yang Menjalankan Fungsi Peradilan menurut Undang-Undang Pemilu. Binamulia Hukum, 12(1), 89-98. https://doi.org/10.37893/jbh.v12i1.347 Kasim, A., & Purnamasari, A. I. (2021). Dekonstruksi Penanganan Pelanggaran Administrasi yang Terstruktur, Sistematis dan Masif dalam Pilkada. Mimbar Hukum, 33(2), 494-520. https://doi.org/10.22146/mh.v33i2.3730 Lesmana, T. (2023). Perlindungan Hukum terhadap Saksi Pelapor (Whistleblower) Tindak Pidana Korupsi di Indonesia. Civilia: Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2(1), 45-53. https://doi.org/10.572349/civilia.v2i2.228 Maria, A. (2023). Peran Bawaslu Daerah sebagai Pengawas dalam Pencegahan dan Penanganan Pelanggaran Administrasi Pemilu di Kota Sukabumi. Rechtsnrmen Jurnal of Law, 1(4), 205-220. https://eprints.ummi.ac.id/3676/ Natalia, S. (2013). Perlindungan Hukum Terhadap Saksi Dan Korban Oleh Lembaga Perlindungan Saksi Dan Korban (LPSK). Lex Crimen, 2(2), 56-64. https://ejournal.unsrat.ac.id/index.php/lexcrimen/article/view/1541 Nugraha, W. (2023). Efektivitas Sistem Informasi Partai Politik (Sipol) dalam Proses Pendaftaran Calon Peserta Pemilu Tahun 2024 berdasarkan Putusan Badan Pengawas Pemilihan Umum (Bawaslu) Nomor: 003/PS. Reg/Bawaslu/X/2022. UNES Law Review, 5(4), 3897-3916. https://doi.org/10.31933/unesrev.v5i4.711 Nurisman, E. (2022). Risalah Tantangan Penegakan Hukum Tindak Pidana Kekerasan Seksual Pasca Lahirnya Undang-Undang Nomor 12 Tahun 2022. Jurnal Pembangunan Hukum Indonesia, 4(2), 170-196. https://doi.org/10.14710/jphi.v4i2.170-196 Purwanda, S. (2020). The Existence of the Right to Books for Frontier, Outermost and Disadvantaged Regions as Part of the Right to Enjoy Education. JL Pol'y & Globalization, 95, 42. https://doi.org/10.7176/JLPG/95-07 Purwanda, S., Ambarwati, A., Darmawati, D., & Prayudi, P. (2024). Haluan Kesejahteraan Sosial dalam Diskursus Teori-Teori Keadilan. Dinamika Hukum, 25(1), 152-161. https://doi.org/10.35315/dh.v25i1.9819